Method for preparing alumina-supported perovskite oxide compositions, alumina-supported perovskite oxide compositions, and uses of said compositions

JP2023501542A5Active Publication Date: 2025-03-14SASOL GERMANY GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022527178
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-11-12
Filing Date
2020-11-12
Publication Date
2025-03-14
Estimated Expiration
2040-11-12

AI Technical Summary

Technical Problem

Existing NOx trap catalysts for lean-burn engines face challenges in storing NOx at low to moderate temperatures without redox activation, leading to substantial fuel penalties due to the redox activity of ceria, and perovskite compounds lack sufficient surface area for effective NOx reaction.

Method used

A method is developed to prepare alumina-supported perovskite oxide compositions by combining boehmite suspensions with aqueous salt solutions, followed by calcination, to achieve uniformly dispersed perovskite crystals with controlled crystallite sizes and improved catalytic properties.

Benefits of technology

The method produces perovskite oxide compositions with high surface area and low crystallite sizes, enhancing NOx storage capacity and reducing fuel penalties by optimizing the catalytic performance in lean-burn engines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000013_0000
    Figure 00000013_0000
  • Figure 00000013_0001
    Figure 00000013_0001
  • Figure 00000013_0002
    Figure 00000013_0002
Patent Text Reader

Abstract

The present disclosure relates to methods for preparing alumina-supported perovskite oxide compositions, alumina-supported perovskite oxide compositions, and the use of said alumina-supported perovskite oxide compositions in catalyst systems for emission control applications.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to a method for preparing a composition of alumina-supported perovskite oxides, a composition of alumina-supported perovskite oxides, and the use of the composition in catalyst systems for emission control applications. [Background technology]

[0002] To reduce the NOx content in the exhaust gas of lean-burn engines, a specific NOx aftertreatment system is required. This is because the reduction of NOx to N2, as is the case with three-way catalysts that mostly operate under stoichiometric conditions, is not possible under current oxidation conditions. Therefore, special exhaust gas aftertreatment catalysts have been developed that contain materials capable of storing NOx, for example, as nitrates / nitrites under dilute conditions. By applying simple stoichiometric conditions or sufficient operating conditions, the stored NOx can be converted to nitrogen, and the storage material is regenerated. Such catalysts are generally referred to as (lean) NOx trap catalysts. NOx trap catalysts can be installed upstream of zeolite-based selective catalytic reduction (SCR) catalysts, which become more efficient at higher temperatures.

[0003] NOx trap catalysts typically contain CeO2 as a storage component, particularly for storing NOx in the low to medium temperature range. A drawback is that during deNOx processes, such as the regeneration of concentrated exhaust gas compositions, a large portion of the reducing agent is consumed due to the redox activity of ceria. Therefore, Ce 3+ Ce 4+ This is reduced to a certain value, resulting in a de facto decrease in fuel efficiency (fuel penalty).

[0004] Therefore, there is a need for the development of materials that can store NOx in the low to medium temperature range, where oxidation-reduction is not activated under operating conditions.

[0005] The chemical formula is ABO3, a perovskite with no redox activity (where A is a rare earth element, alkaline earth element, alkali, Pb 2+ , and Bi 3+ While B is a cation containing a transition metal, B is an attractive alternative. However, this compound typically does not have the surface area necessary to react with NOx in a bulk state.

[0006] The use of perovskites in catalytic systems for exhaust gas emissions is disclosed in Patent Document 1. This patent discloses a composite of lanthanum-based perovskites on a support made of alumina or aluminum oxyhydroxide. The composite is produced by a precipitation step, which produces a perovskite more advantageous than the prior art. The necessity and importance of low crystallinity of the perovskite is taught in paragraph 3, in that Patent Document 1 states that the perovskite can be dispersed as finely as possible on the support, in other words, it can be provided in the form of fine particles. However, the low crystallinity required for certain catalytic applications cannot be obtained by the method described in Patent Document 1.

[0007] Patent Document 2 discloses a two-step process for preparing an oxide support mixed with a perovskite. In Example 5, the LaAlO3 powder is prepared in the first step from γ-alumina and lanthanum nitrate. The LaAlO3 is mixed with an aqueous solution of a perovskite precursor compound, dried, and calcined. Thus, the LaAlO3 coexists with the catalytic component of the perovskite material.

[0008] Patent Document 3 discloses a two-step process for preparing a carrier of an oxide mixed with perovskite. In Example 1, γ-alumina is impregnated with lanthanum nitrate in the first step. The stabilized alumina is impregnated three times with an aqueous solution of a perovskite precursor compound, dried, and calcined. Although the crystallite size is not reported, the relatively sharp reflections in the X-ray diffraction pattern indicate that the perovskite crystallites are larger than 5 nm.

Prior Art Documents

Patent Documents

[0009]

Patent Document 1

Patent Document 2

Patent Document 3

Summary of the Invention

Problems to be Solved by the Invention

[0010] As described above, there is still a need to develop a composite of a perovskite-type oxide with a perovskite structure on an alumina carrier, with improved properties.

Means for Solving the Problems

[0011] According to a first aspect of the present disclosure, a method for preparing a composition of a perovskite-type oxide supported on alumina is provided, the method comprising: (i) a step of providing doped alumina, wherein the doped alumina is a. one containing alumina and a rare earth oxide, b. one containing alumina and an alkaline earth oxide, or c. one containing alumina and a mixture of a rare earth oxide and an alkaline earth oxide and the doped alumina is (A) Preparing a boehmite suspension containing boehmite; (B) Preparing an aqueous solution of a salt, wherein the aqueous solution of the salt is a. a rare earth salt, b. an alkaline earth salt, or c. a mixture of a rare earth salt and an alkaline earth salt including; (C) Combining the boehmite suspension with the aqueous solution of the salt to form a mixture of boehmite salts; (D) Drying the mixture of boehmite salts to form a dried product of the mixture of boehmite salts; (E) Calcining the dried product of the mixture of boehmite salts to produce doped alumina including the steps provided by the method; (ii) Impregnating the provided doped alumina with a water-soluble impregnating solution containing one of a water-soluble rare earth salt, a water-soluble alkaline earth salt, a water-soluble alkali salt, a water-soluble salt of Bi 3+ , a water-soluble salt of Pb 2+ , and a water-soluble transition metal salt, or a mixture of these salts, to form an impregnated body of doped alumina; (iii) Calcining the impregnated body of doped alumina to obtain a composition of a perovskite-type oxide supported with alumina including.

[0012] Boehmite is defined as any alumina with the molecular formula AlOOH*xH2O, where x is from 0 to 0.5, and includes boehmite and pseudoboehmite.

[0013] The boehmite suspension may further include silica, titania, a water-soluble salt of titanium or zirconium, or a mixture thereof.

[0014] The boehmite suspension preferably contains a boehmite precursor and at least water in a ratio of 2:98 to 20:80. The boehmite suspension selectively contains an additive for adjusting the pH, such as a carboxylic acid or ammonia.

[0015] More preferably, the boehmite suspension is prepared by hydrolysis of an aluminum alkoxide.

[0016] An aqueous solution of salt for preparing doped alumina preferably comprises water and at least a water-soluble rare earth salt, a water-soluble alkaline earth salt, or a mixture thereof. The rare earth salt is preferably an acetate or nitrate of an element with atomic number 57 to 60, most preferably an acetate of La. The alkaline earth salt is preferably an acetate or nitrate of an alkaline earth element. The alkaline earth salt is preferably an acetate of Ca, Sr, or Ba, most preferably an acetate of Sr.

[0017] The doped alumina (after calcination) has a maximum content of 20% by weight or less, preferably less than 12% by weight, and most preferably less than 10% by weight, of rare earth oxides, alkaline earth oxides, or mixtures thereof. Of the rare earth oxides, alkaline earth oxides, or mixtures thereof present in the alumina-supported perovskite oxide composition, 50% by weight or more, preferably 90% by weight or more, and most preferably 100% by weight, are added to the boehmite suspension as rare earth salts, alkaline earth salts, or mixtures thereof. The oxides are produced from the salts by calcination. The doped alumina provides uniformly dispersed nucleation sites in the process of impregnating the doped alumina with a water-soluble impregnation solution to obtain an alumina-supported perovskite oxide composition.

[0018] In particular, when the doped alumina (after calcination) contains lanthanum oxide, the maximum content of lanthanum oxide is 20% by weight or more, preferably less than 12% by weight, and most preferably less than 10% by weight. Lanthanum oxide is produced from lanthanum salts by calcination. Due to the low content of lanthanum oxide, LaAlO3 is not formed in the alumina-supported perovskite-type oxide composition.

[0019] The mixture of boehmite salts is preferably spray-dried to produce a dried body of the boehmite salt mixture.

[0020] The dried mixture of boehmite salts is calcined at a temperature of preferably 450°C to 1200°C, preferably 500°C to 600°C, for 0.5 hours or more, more preferably 0.5 to 5 hours, to produce doped alumina. The temperature and time are selected independently.

[0021] The impregnation of doped alumina can be carried out by any impregnation method known in the art, preferably by initial wet impregnation. In the above method, 80-100% of the pore volume of the doped alumina is generally impregnated with a water-soluble impregnation solution.

[0022] The water-soluble impregnation solution contains a mixture of water-soluble salts according to a specific stoichiometric ratio of the perovskite-type oxide with chemical formula ABO3.

[0023] The one or more water-soluble salts in the water-soluble impregnation solution are preferably rare earth element acetates or nitrates, preferably rare earth elements with atomic numbers 57 to 60, more preferably La acetates or nitrates, alkaline earth element acetates or nitrates, preferably Sr, Ba, and Ca acetates or nitrates, more preferably Sr acetates or nitrates, Pb 2+ and / or Bi 3+ The aqueous transition metal salts include acetates or nitrates of ammonium citrate, ammonium titanium lactate, zirconium acetate, or mixtures thereof. More preferably, the aqueous salts are zirconium acetate, ammonium iron citrate, and ammonium titanium lactate.

[0024] Step (ii) of a first aspect of the present disclosure provides a water-soluble impregnation solution comprising a mixture of water-soluble salts. The water-soluble salts are: (a) Acetates or nitrates of rare earth elements, preferably acetates or nitrates of rare earth elements with atomic numbers 57 to 60, more preferably acetates or nitrates of La, (b) An acetate or nitrate of an alkaline earth element, preferably an acetate or nitrate of one or more of Sr, Ba, and Ca, more preferably an acetate or nitrate of Sr, and (c) Pb 2+ and Bi 3+ one or more acetates or nitrates of one or more salts of, and (d) One or more water-soluble transition metal salts such as, for example, ammonium iron citrate, ammonium titanium lactate, ammonium iron citrate, zirconium acetate, or mixtures thereof, such as transition metal salts of Fe, Ti, and / or Zr one or more salts of can include a mixture of.

[0025] Alternatively, the water-soluble impregnation solution can include only one water-soluble salt, such as ammonium iron citrate.

[0026] By using the doped alumina, preferably only one impregnation step is applied to obtain an impregnated body of doped alumina with a high loading capacity by impregnation.

[0027] The impregnated body of doped alumina is preferably calcined at a temperature of 500°C to 1,100°C, most preferably at a temperature of 700°C to 1,000°C. The calcination can be carried out over a period of 0.5 hours or more, more preferably 0.5 to 5 hours, for example 3 hours. The temperature and time are selected independently. By the uniformly dispersed impregnated body obtained in step (ii), a composition of a perovskite-type oxide supported on alumina with a very low perovskite crystallite size is obtained.

[0028] According to a second aspect of the present disclosure, there is provided a composition of a perovskite-type oxide supported on alumina prepared according to the method of the present disclosure.

[0029] According to a third aspect of the present disclosure, (i) 50 weight percent or more, preferably 75 to 95 weight percent of doped alumina, and (ii) Chemical formula I ABO3(I) 5 to 50 weight percent, preferably 5 to 25 weight percent, of a perovskite-type oxide and Includes, A consists of rare earth elements, alkaline earth elements, alkali elements, and Pb. 2+ , Bi 3+ , or mixtures thereof, B comprises one or more transition metals, including a mixture of transition metals. The crystallite size of ABO3 is preferably less than 5 nm after sintering at 850°C for 3 hours or after firing, preferably between 4 nm and 5 nm, and is characterized by being less than 2 nm after sintering at 700°C for 4 hours or after firing. A composite of a perovskite-type oxide composition supported with alumina is provided.

[0030] The weighted intensity ratio of alumina-supported perovskite oxide compositions is characterized by being less than 10, preferably less than 8. The weighted intensity ratio is determined by Equation 1. The X-ray diffraction pattern of the perovskite structure using copper Kα emission at a wavelength of 1.54 Å includes a strong reflection at 2θ of approximately 32 degrees.

[0031] The X-ray diffraction pattern of transition alumina includes strong reflections at 2θ of approximately 46.

[0032] The weighted intensity ratio R (see Equation 1) is a measure of the crystallinity of the perovskite material on the alumina support. R=[(I 32 / I 46 )] / m p (Formula 1) I 32 Reflectance at approximately 32 degrees I 46 Reflectance at approximately 46 degrees m p : Perovskite mass / ((Perovskite mass calculated as ABO3) + Alumina mass)

[0033] Doped alumina is defined and prepared under the first aspect of this disclosure. A composition of alumina-supported perovskite oxide preferably contains 80 weight percent or more of doped alumina.

[0034] Preferably, A in the perovskite oxide according to formula I comprises an alkaline earth element, more preferably a mixture of one or more Sr, Ba or Ca and a rare earth element, even more preferably an element with atomic number 57 to 60. Most preferably, A comprises a mixture of Sr and La.

[0035] Preferably, B in the perovskite oxide according to formula I comprises a mixture of two distinct transition metals, preferably a mixture of Fe and one or more elements from group IVa of the periodic table. More preferably, B comprises a mixture of Fe, Ti, and Zr.

[0036] Components A and B are independently selected such that the sum of the oxidation states of the individual components, weighted by their molar ratios, equals +6, in order to achieve charge equilibrium with the anions of the three oxides.

[0037] The perovskite oxide is preferably uniformly dispersed in an alumina substrate, both of which produce alumina-supported perovskite oxide compositions. Although not theoretically linked, the applicant believes that the uniform dispersion of small crystals of the perovskite oxide allows the alumina substrate to act as a diffusion barrier, resulting in the beneficial properties of the alumina-supported perovskite oxide composite.

[0038] The BET specific surface area of ​​a perovskite oxide composition supported with alumina is 50 m². 2 / g~300m 2 / g, preferably 100m 2 / g~200m 2 The volume can be adjusted to 0.1 ml / g to 1.5 ml / g, preferably 0.5 ml / g to 1.0 ml / g.

[0039] Next, the present disclosure will be described with reference to the following non-limiting embodiments and drawings. [Brief explanation of the drawing]

[0040] [Figure 1] Figure 1 shows the X-ray diffraction patterns of Example 1 after firing at 700°C for 4 hours and after firing at 850°C for 3 hours. Reflections marked with an asterisk (*) indicate the X-ray pattern reflection of the perovskite-type oxide. [Figure 2] Figure 2 shows the X-ray diffraction patterns of Example 2 after firing at 700°C for 4 hours and after firing at 850°C for 3 hours. The X-ray diffraction patterns are shown, and reflections marked with an asterisk (*) indicate the X-ray pattern reflection of the perovskite-type oxide. [Figure 3] Figure 3 shows the X-ray diffraction patterns of Example 2 and Comparative Example 1 after baking at 700°C for 4 hours and after baking at 850°C for 3 hours. [Figure 4] Figure 4 shows the X-ray diffraction patterns of Example 2 and Comparative Example 2 after firing at 700°C for 4 hours and at 850°C for 3 hours. Reflections marked with an asterisk (*) indicate the X-ray pattern of perovskite-type oxides, reflections marked with a hash (#) indicate the X-ray pattern of SrAl2O4, and reflections marked with a plus sign (+) indicate the X-ray pattern of SrCO3. [Figure 5] Figure 5 shows the X-ray diffraction patterns of Example 3 and Comparative Example 3 after firing at a temperature of 700°C for 4 hours. Reflections marked with an asterisk (*) indicate the X-ray patterns of perovskite-type oxides. [Modes for carrying out the invention]

[0041] Uniformity is measured by image processing of cross-sections using a scanning electron microscope (SEM), and selectively, along with elemental mapping using energy dispersive X-ray analysis (EDX) to reveal the size of the doped alumina and perovskite oxide regions.

[0042] (022) The crystal size of the perovskite oxide is determined using the Debye-Scherrer method, which analyzes the reflection (in the Fm-3c space group). The crystal size is less than 5 nm when measured after calcination at 850°C for 3 hours, and less than 2 nm when measured after calcination at 700°C for 3 hours.

[0043] Specific surface area and pore volume are measured at liquid nitrogen temperature by N2 physicoadsorption using a common volumetric measuring device such as Quadrasorb from Quantachrome. Specific surface area is determined using the BET theory (DIN ISO 9277), and pore volume is determined according to DIN 66131. [Examples]

[0044] [Example 1] (20% by weight perovskite La 0.5 Sr 0.5 Fe 0.5 Ti 0.5 (A complex using O3) Gamma alumina containing 10 wt percent La2O3 was prepared by mixing an aqueous solution of lanthanum acetate with a 5 wt percent boehmite suspension in water. The mixture was then spray-dried and calcined at 500°C for 1 hour.

[0045] La-doped alumina was initially impregnated by wetting with a mixed solution of Sr acetate, ammonium iron citrate, and Tyzor LA (titanium solution), and after calcination, it reached loadings of 4.8 wt% SrO, 3.8 wt% Fe2O3, and 3.8 wt% TiO2. The products were calcined at 850°C for 3 hours and at 700°C for 4 hours, respectively.

[0046] Figure 1 shows the X-ray diffraction patterns of the material obtained in Example 1 after calcination at 850°C for 3 hours and at 700°C for 4 hours.

[0047] [Example 2] (20% by weight perovskite La 0.5 Sr 0.5 Fe 0.5 Zr 0.5 (A complex using O3) Gamma alumina containing 7.8 wt percent La2O3 was prepared by mixing an aqueous solution of lanthanum acetate with a 5 wt percent boehmite suspension in water. The mixture was then spray-dried and calcined at 500°C for 1 hour.

[0048] Doped alumina was impregnated by initial wetting with a mixed solution of ammonium iron citrate and Sr acetate to loads of 3.4 wt% Fe2O3, 5.3 wt% ZrO2, and 4.4 wt% SrO. The products were calcined at 850°C for 3 hours and 700°C for 4 hours, respectively.

[0049] The X-ray diffraction patterns of the materials obtained after calcination at 850°C for 3 hours and after calcination at 700°C for 4 hours are shown in Figure 2.

[0050] [Comparative Example 1] (20% by weight perovskite La 0.5 Sr 0.5 Fe 0.5 Ti 0.5 (A complex containing O3) The composite was prepared according to Example 5 of Patent Document 2.

[0051] First, LaAlO3 powder was synthesized by adding 100.9 g of γ-alumina to 400 ml of an aqueous solution of 425 g of lanthanum nitrate hexahydrate. The resulting mixture was evaporated and dried. The mixture was then calcined in air at 600°C for 3 hours and then at 900°C for 8 hours to obtain LaAlO3 powder.

[0052] In the next step, the LaAlO3 powder was mixed with aqueous solutions of strontium, iron, and zirconium nitrates and calcined to a composite containing 3.4 wt percent Fe2O3, 5.3 wt percent ZrO2, 4.4 wt percent SrO, and a further 6.9 wt percent La2O3. The resulting mixture was dried in air at 110°C for 10 hours and calcined at 700°C for 4 hours and 850°C for 3 hours, respectively.

[0053] The X-ray diffraction patterns of the materials obtained after calcination at 850°C for 3 hours and after calcination at 700°C for 4 hours are shown in Figure 3.

[0054] These results indicate that the obtained product differs from the composition of the present disclosure in that it is absent from alumina, has a large perovskite crystal size, and has a substantially small specific surface area.

[0055] [Comparative Example 2] (20% by weight perovskite La 0.5 Sr 0.5 Fe 0.5 Ti 0.5 (A complex using O3) The composite was prepared according to Example 6 of Patent Document 3.

[0056] 25 g of γ-alumina beads were impregnated twice with aqueous solutions containing large amounts of lanthanum, strontium, iron, and zirconium nitrates, and calcined to a composite with a load of 6.9 wt% La2O3, 3.4 wt% Fe2O3, 5.3 wt% ZrO2, and 4.4 wt% SrO in 5 g of ethanol and 10 g of citric acid. The resulting material was dried under vacuum after the first impregnation (to remove the solution). After the second impregnation, the product was calcined at 700°C for 4 hours and at 850°C for 3 hours, respectively.

[0057] The X-ray diffraction patterns of the materials obtained after calcination at 850°C for 3 hours and after calcination at 700°C for 4 hours are shown in Figure 4.

[0058] The powder X-ray diffraction pattern reveals a phase significantly different from that of the composition of this disclosure. Specifically, strontium does not form part of the perovskite structure, but instead exists in the form of SrCO3 after calcination at 700°C and in the form of SrAl2O4 after calcination at 850°C. Therefore, it can be concluded that this procedure is not suitable for producing the desired composition. These results are included in Table 1 below.

[0059] [Table 1]

[0060] [Example 3] (Composite using 10 wt percent perovskite LaFeO3) γ-alumina containing 11.7 wt percent La2O3 was prepared by mixing an aqueous solution of lanthanum acetate with a 5 wt percent boehmite suspension in water. The mixture was then spray-dried and calcined at 500°C for 1 hour.

[0061] Doped alumina was impregnated by initial wetting with an aqueous solution of ammonium iron citrate to a load of 3.3 wt% Fe2O3. The products were calcined at 850°C for 3 hours and at 700°C for 4 hours, respectively.

[0062] The X-ray diffraction pattern of the material obtained after calcination at 700°C for 4 hours is shown in Figure 5.

[0063] [Comparative Example 3] (A composite containing 10 wt percent perovskite LaFeO3) The composite was prepared according to Example 3 of Patent Document 1.

[0064] A mixture of 2.2 g of iron acetate in 75 ml of water and 4.46 g of lanthanum acetate in 75 ml of water was mixed and added to a dispersion prepared by mixing 27 g of lanthanum-doped alumina (commercially available as PURALOX TH100 / 150 L4) with 150 ml of water. 11.2 g of 25% NH3 solution was added to the mixture to bring the pH to 10. After stirring for 1.5 hours, the precipitate was filtered, and the resulting powder was calcined at 700°C for 4 hours.

[0065] The X-ray diffraction pattern of the material obtained after calcination at 700°C for 4 hours is shown in Figure 5.

[0066] A comparison of the X-ray diffraction patterns of the materials in Example 3 and Comparative Example 3 clearly demonstrates the difference in the crystallinity of the perovskite phase.

[0067] The crystalline perovskite phase can be detected for Comparative Example 3, as indicated by the asterisk in Figure 2, but the reflectance of the perovskite is very weak. Therefore, it can be concluded that the perovskite phase exists mostly in an X-ray amorphous state.

[0068] The results are included in Table 2 below.

[0069] [Table 2]

Claims

1. 1. A method for preparing an alumina-supported perovskite oxide composition, comprising: (i) providing a doped alumina, said doped alumina comprising: a. Contains alumina and rare earth oxides, b. Containing alumina and alkaline earth oxides, or c. Alumina and a mixture of rare earth oxides and alkaline earth oxides and the doped alumina is (A) preparing a boehmite suspension containing boehmite; (B) preparing an aqueous solution of a salt, the aqueous solution of the salt comprising: a. Rare earth salts, b. an alkaline earth salt, or c. A mixture of rare earth salts and alkaline earth salts and (C) combining the boehmite suspension with the aqueous salt solution to form a boehmite salt mixture; (D) drying the boehmite salt mixture to produce a dried body of the boehmite salt mixture; (E) calcining the dried body of the boehmite salt mixture to produce the doped alumina; and a step provided by a method comprising at least (ii) The doped alumina is dissolved in a water-soluble rare earth salt, a water-soluble alkaline earth salt, a water-soluble alkali salt, a water-soluble Bi 3+ salts, water-soluble Pb 2+ and a water-soluble transition metal salt, or a mixture of such salts, to form the doped alumina impregnated body; (iii) calcining the impregnated body of the doped alumina; A method comprising:

2. The boehmite suspension further comprises silica, titania, a water-soluble alkaline earth metal salt, a water-soluble rare earth metal salt, zirconium, or a mixture thereof. The method of claim 1.

3. The aqueous salt solution contains at least water and a water-soluble rare earth salt, a water-soluble alkaline earth salt, or a mixture thereof.

3. The method according to claim 1 or 2.

4. The impregnation of the doped alumina comprises incipient wetness impregnation. The method according to any one of claims 1 to 3.

5. 80-100% of the pore volume of the doped alumina is impregnated with the aqueous impregnation solution. The method according to any one of claims 1 to 4.

6. The water-soluble salt is (a) acetates or nitrates of rare earth elements, preferably acetates or nitrates of rare earth elements having atomic numbers from 57 to 60, more preferably acetates or nitrates of La; (b) an acetate or nitrate of an alkaline earth element, preferably an acetate or nitrate of one or more of Sr, Ba, and Ca, more preferably an acetate or nitrate of Sr; and (c) Pb 2+ and Bi 3+ One or more acetates or nitrates of and one or more salts of (d) one or more water-soluble transition metal salts, including ammonium iron citrate, ammonium titanium lactate, zirconium acetate, or mixtures thereof; and one or more salts of Contains a mixture of The method according to any one of claims 1 to 5.

7. The impregnated body of the doped alumina is calcined at a temperature of 500°C to 1100°C, preferably 700°C to 1000°C, for at least 0.5 hours, more preferably 0.5 to 5 hours. The method according to any one of claims 1 to 6.

8. Prepared by the method according to any one of claims 1 to 7 Alumina-supported perovskite oxide compositions.

9. (i) 50 weight percent or more of doped alumina; (ii) 5 to 50 weight percent of a compound of the formula ABO 3 Perovskite oxides and Including, A is a rare earth element, an alkaline earth element, an alkali element, or Pb 2+ , Bi 3+ or mixtures thereof, B comprises a transition metal, including a mixture of transition metals; ABO 3 The crystallite size of is characterized as less than 5 nm after calcination at 850°C for 3 hours and less than 2 nm after calcination at 700°C for 4 hours. A composite of an alumina-supported perovskite oxide composition.

10. The weighted intensity ratio R is less than 10, preferably less than 8, calculated from reflections in an X-ray diffraction pattern of the composition at 2θ of about 32 degrees and 2θ of about 46 degrees, obtained by emitting copper Kα radiation having a wavelength of 1.54 Å; R = [(I 32 / I 46 )] / m p (Equation 1) and I 32 is the intensity of the reflection at about 32 degrees, I 46 is the intensity of the reflection at about 46 degrees, m p but, Mass of perovskite / ((ABO 3 (calculated as) mass of perovskite + mass of alumina) It is calculated from Equation 1:

10. The alumina-supported perovskite oxide composition of claim 8 or 9.

11. A is, one alkaline earth element, preferably one or more of Sr, Ba, Ca, One rare earth element, more preferably an element with an atomic number of 57 to 60, Contains a mixture of The alumina-supported perovskite oxide composition according to any one of claims 8 to 10.

12. B comprises a mixture of two distinct transition metals, preferably Fe and an element from Group IVa of the Periodic Table of the Elements.

12. The alumina-supported perovskite oxide composition according to any one of claims 8 to 11.

13. Specific surface area: 50 to 300 m 2 / g, preferably 100 to 200 m 2 / g and further characterized by a pore volume of 0.1 to 1.5 ml / g, preferably 0.5 to 1.0 ml / g.

13. The alumina-supported perovskite oxide composition according to any one of claims 8 to 12.

14. Obtained by the method according to any one of claims 1 to 7 The alumina-supported perovskite oxide composition according to any one of claims 8 to 13.

15. The doped alumina is LaAlO 3 does not include 15. The alumina-supported perovskite oxide composition according to any one of claims 8 to 14.

16. Catalyst systems for emission control applications, particularly NOx trap catalysts Use of the alumina supported perovskite oxide composition according to any one of claims 8 to 14.